2009
DOI: 10.1016/j.apmr.2008.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation and Physical Activity During Rehabilitation and Future Functional Outcomes in Patients After Hip Fracture

Abstract: Objective We examined the association between physical activity recorded by Actigraphy during therapy sessions (therapy) to therapist rated patient participation and self reported future functional outcomes. We hypothesized those participants who were more active during rehab would have higher participation scores and better functional outcomes following hip fracture compared to those who were less active. Design Longitudinal study with 3 and 6 month follow-up. Setting Participants were recruited from skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 29 publications
3
75
0
2
Order By: Relevance
“…None of the participants were followed-up for the home exercise program. Variation in the rehabilitation activities and lack of guidelines for mobility limitation and disability prevention after hip fracture has been recognized worldwide [47,48]. It has been suggested that better functional outcomes could be achieved with more intensive rehabilitation and promotion of physical activity after hip fracture [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…None of the participants were followed-up for the home exercise program. Variation in the rehabilitation activities and lack of guidelines for mobility limitation and disability prevention after hip fracture has been recognized worldwide [47,48]. It has been suggested that better functional outcomes could be achieved with more intensive rehabilitation and promotion of physical activity after hip fracture [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…119 The majority of the studies included participants who were mobile and living independently in their own home or in a care home before their hip fracture. 12 [183][184][185][186]191,193,194,196,197,199,201 Only seven studies included patients with a medical or psychological comorbidity; 123,139,145,157,158,184,193 the majority of studies excluded such patients, especially when exercise would have been contraindicated. Only two studies included patients who had a history of a previous fracture.…”
Section: A Community-based Multidisciplinary Rehabilitation Package Fmentioning
confidence: 99%
“…185 Eight studies included patients aged ≥ 50 years; 87,98,103,118,173,187,188,192 18 studies included patients aged ≥ 60 years; 12,89,96,104,114,117,119,122,132,133,149,154,164,[193][194][195][196][197] 19 studies included patients aged ≥ 70 years; 69,72,79,88,106,108,110,111,116,120,131,136,143,148,150,161,180,183,184 and seven studies included patients aged ≥ 80 years. 13,81,123,134,137,152,178 The age of the included participants could not be determined from the study reports for four studies.…”
Section: A Community-based Multidisciplinary Rehabilitation Package Fmentioning
confidence: 99%
“…6,7 In 33 addition to beneficial long-term effects of physical activity on the prevention and treatment of 34 several chronic diseases, 8 physical activity has shown to have positive short-term effects on…”
mentioning
confidence: 99%